Biomimetic silk biomaterials: Perlecan-functionalized silk fibroin for use in blood-contacting devices. (15th September 2021) - Lau, Kieran; Waterhouse, Anna; Akhavan, Behnam; Gao, Lingzi; Kim, Ha Na; Tang, Fengying; Whitelock, John M; Bilek, Marcela M; Lord, Megan S; Rnjak-Kovacina, Jelena
Abstract: Blood compatible materials are required for the development of therapeutic and diagnostic blood contacting devices as blood-material interactions are a key factor dictating device functionality. In this work, we explored biofunctionalization of silk biomaterials with a recombinantly expressed domain V of the human basement membrane proteoglycan perlecan (rDV) towards the development of blood compatible surfaces. Perlecan and rDV are of interest in vascular device development as they uniquely support endothelial cell, while inhibiting smooth muscle cell and platelet interactions. rDV was covalently immobilized on silk biomaterials using plasma immersion ion implantation (PIII), a new method of immobilizing proteins on silk biomaterials that does not rely on modification of specific amino acids in the silk protein chain, and compared to physisorbed and carbodiimide immobilized rDV. Untreated and treated silk biomaterials were examined for interactions with blood components with varying degrees of complexity, including isolated platelets, platelet rich plasma, blood plasma, and whole blood, both under agitated and flow conditions. rDV-biofunctionalized silk biomaterials were shown to be blood compatible in terms of platelet and whole blood interactions and the PIII treatment was shown to be an effective and efficient means of covalently immobilizing rDV in its bioactive form. These biomimetic silk biomaterials are a promising platform toward development of silk-based blood-contacting devices for therapeutic, diagnostic, and research applications. Statement of significance: Blood compatible materials are required for the development of therapeutic and diagnostic blood contacting devices as blood-material interactions are a key factor dictating device functionality. In this work, we explored biofunctionalization of silk biomaterials with a recombinantly expressed domain V (rDV) of the human basement membrane proteoglycan perlecan towards the development of blood compatible surfaces. Perlecan and rDV are of interest in vascular device development as they uniquely support endothelial cell, while inhibiting smooth muscle cell and platelet interactions. rDV was covalently immobilized on silk biomaterials using plasma immersion ion implantation (PIII), a new method of immobilizing proteins on silk biomaterials that does not rely on modification of specific amino acids in the silk protein chain. These biomimetic silk biomaterials are a promising platform toward development of silk-based blood-contacting devices for therapeutic, diagnostic, and research applications. Graphical abstract: Image, graphical abstract